Criminal Liability for the Spread of Deep Fake-Based Pornographic Content on Social Media - Rangga Agin Wijaya; Endang Sutrisno; M. Noupel (Devotion : Journal of Research and Community Service, 2026)
The development of artificial intelligence (AI) technology has given rise to various digital innovations, one of which is deepfake technology, which can manipulate images, videos, or audio to make them appear authentic. In addition to providing benefits, this technology also has the potential to be misused to create and disseminate pornographic content without the victim’s consent. Such actions can harm the victim’s honor, privacy, reputation, and psychological well-being, thereby creating legal issues that require adequate regulation and enforcement. This study aims to analyze the legal regulation and criminal liability of perpetrators involved in the dissemination of deepfake-based pornographic content in Indonesia. The method used is normative legal research with statutory and conceptual approaches. The research data were obtained through a literature review of laws and regulations, legal literature, scientific journals, and other relevant legal sources, and were then analyzed qualitatively. The results of the study show that the dissemination of deepfake-based pornographic content essentially fulfills the elements of a criminal offense and that perpetrators may be held criminally liable. Although there is no specific regulation on deepfakes, these acts may be prosecuted under the Pornography Law, the Electronic Information and Transactions Law, the Criminal Code, and the Personal Data Protection Law. However, law enforcement still faces obstacles related to regulatory limitations, digital evidence, and the identification of perpetrators. Therefore, more adaptive legal reform and the strengthening of law enforcement capacity are needed to ensure legal certainty and effective protection for victims.